TYPOLOGY OF PRIVATE CAR USERS DURING COVID-19 PANDEMIC IN KAYURINGIN JAYA - Dewi, Diah Intan Kusumo; Hafizha, Jihan; Rakhmatulloh, Anita Ratnasari (Universitas Ibn Khaldun Bogor, 2022)
The Covid-19 Pandemic was indicated in March 2020, which has changed people's daily activities patterns. Implementing the restricting regulation imposed by the government made some of the people's daily activities diverted to an online system. As a result, community mobility has decreased, especially on private car usage. However, there is a shift in vehicle usage which many people are starting to switch their mode to the private car in daily travel. This condition was predicted would continue even after the Pandemic ends. The increase in private car usage will worsen the congestion than before the Covid-19 Pandemic appropriate steps and handling are needed to prevent the increase in congestion. One of them is by knowing the characteristics and journeys of private car users during the Covid-19 Pandemic. This research is a typology of private car users during the Covid-19 Pandemic to identify the similarities and differences in the characteristics possessed by each private car user through the typological groups formed. Through this research, it can be seen the movement patterns and characteristics of the people who use private cars. This study uses the Hierarchical Cluster Analysis method. The analysis is based on several variables such as private car usage frequency variables, socioeconomic characteristics variables, demographic variables, household variables, and household travel patterns object of this research is 107 households which are owners and use of private cars for further analysis and form clusters of private car users that have the same characteristics of each cluster. The typology of private car users is compiled based on the unique characteristics possessed by each cluster that is formed. The results of this study are 8 typologies of private car users, which are divided from intensive users to irregular users. Typology 1 has the largest number of respondents and dominates the frequency of trips by private car users. The benefit of this research for the government is as input in the formulation of policies to regulate the use of private cars so that the policies taken by the government can be right on target